Impact of Prenatal Selective Serotonin Reuptake Inhibitor Antidepressant Exposure and Maternal Mood on Physical Activity, Dietary Intake, and Markers of Adiposity at Age 6 Years. Issue 4 (May 2019) - Hutchison, Sarah M.; Mâsse, Louise C.; Glier, Melissa B.; Brain, Ursula; Devlin, Angela M.; Oberlander, Tim F.
ABSTRACT: Objective: This study assessed associations between maternal depressive symptoms, prenatal maternal antidepressant treatment, maternal estimates of child physical activity (PA), dietary total intake, and markers of adiposity. Methods: Mothers and their children (N = 116) were part of a longitudinal cohort study examining the effects of prenatal exposure to selective serotonin reuptake inhibitor (SSRI) antidepressants and maternal depression (SSRI exposed, n = 42; nonexposed, n = 74). Maternal depression symptoms were assessed prenatally and postnatally. At 6 years, PA was assessed using maternal report, 3-day dietary total intakes were obtained using objective records of intake, portion sizes, and product brand names, and birth weight, weight, height, and waist circumference (WC) at age 6 years were also collected. Body mass index (BMI) and WC z-scores standardized for sex and age were computed as markers of adiposity. Results: Children with SSRI exposure had lower levels of PA than children without SSRI exposure. Total dietary energy intakes did not vary between exposure groups. SSRI exposure was not associated with BMI or WC z-scores of the children. Importantly, although lower birth weight was observed in SSRI-exposed children, differences did not remain, accounting for gestational age. Conclusion: Although SSRI exposure was associated with lower estimates of PA, such exposure was not associated with markers of adiposity or total diet energy intake at age 6 years. The implications across subsequent measures in childhood remain to be determined.